2012
DOI: 10.1242/dev.076687
|View full text |Cite
|
Sign up to set email alerts
|

Histone recognition and nuclear receptor co-activator functions ofDrosophilaCara Mitad, a homolog of the N-terminal portion of mammalian MLL2 and MLL3

Abstract: SUMMARYMLL2 and MLL3 histone lysine methyltransferases are conserved components of COMPASS-like co-activator complexes. In vertebrates, the paralogous MLL2 and MLL3 contain multiple domains required for epigenetic reading and writing of the histone code involved in hormone-stimulated gene programming, including receptor-binding motifs, SET methyltransferase, HMG and PHD domains. The genes encoding MLL2 and MLL3 arose from a common ancestor. Phylogenetic analyses reveal that the ancestral gene underwent a fissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 88 publications
2
48
1
Order By: Relevance
“…We identified Drosophila COMPASS family member Trr as a major H3K4 monomethylase functioning at the enhancer regions and showed that it is required in enhancer-promoter communication for faithful and tissue-specific gene expression (16,21). While Trr has long been considered a divergent form of MLL3 and MLL4 with homology restricted to the C-terminal halves of these proteins, it was recently found that a second gene encodes a protein with homology to the N-terminal halves of MLL3 and MLL4 (14,37). This protein, named Lpt, associates with Trr in a COMPASS-like complex and is also required for bulk H3K4me1 (14,21).…”
Section: Discussionmentioning
confidence: 99%
“…We identified Drosophila COMPASS family member Trr as a major H3K4 monomethylase functioning at the enhancer regions and showed that it is required in enhancer-promoter communication for faithful and tissue-specific gene expression (16,21). While Trr has long been considered a divergent form of MLL3 and MLL4 with homology restricted to the C-terminal halves of these proteins, it was recently found that a second gene encodes a protein with homology to the N-terminal halves of MLL3 and MLL4 (14,37). This protein, named Lpt, associates with Trr in a COMPASS-like complex and is also required for bulk H3K4me1 (14,21).…”
Section: Discussionmentioning
confidence: 99%
“…MLL1 and MLL4 are human orthologs of TRX, and MLL2/ALR and MLL3 are human orthologs of TRR (Ardehali et al, 2011;Chauhan et al, 2012) (supplementary material Fig. S5).…”
Section: Conserved Monomethylation Of H3k4 By Trr and Human Mll1 And mentioning
confidence: 99%
“…These six come in three pairs: Setd1a and Setd1b, which are orthologous to the sole yeast H3K4 methyltransferase Set1 (Roguev et al, 2001); Mll1 (Kmt2a) and Mll2, which are homologous to Drosophila Trithorax (Francis and Kingston, 2001), and Mll3 (Kmt2c) and Mll4 (Kmt2d), which are homologous to a fusion of Drosophila Cara Mitad (Lpt) and trithorax-related (Chauhan et al, 2012;Herz et al, 2012). Each of the six appears to reside in its own protein complex.…”
Section: Introductionmentioning
confidence: 99%